Organ preservation in rectal adenocarcinoma: safety in the regional setting - Watter, Henry K.; Simpson, Fraser; Lamparelli, Michael; Bhorat, Naseem (International Surgery Journal, 2025)
Background: The ‘watch and wait’ (W&W) approach to rectal cancer patients with a complete clinico-radiological response to neoadjuvant treatment is safe when implemented appropriately. However, patients that are not enrolled and surveilled appropriately, have increased risks of local recurrence, metastases and mortality. Regional colorectal units have additional barriers to surveillance, compared to metropolitan equivalents including increased distances to services and poorer health literacy. Methods: This retrospective cohort study assessed enrolment and surveillance of W&W rectal cancer patients by a regional colorectal multidisciplinary team (MDT) and surgical department. Patients enrolled in a W&W protocol via this regional MDT between 2020 and 2024, were included. Adherence to accepted enrolment criteria and the established surveillance protocol was assessed, with particular focus on flexible sigmoidoscopy, MRI and CT/PET. Results: Seven patients achieved complete response and were assigned to the W&W protocol. All were enrolled with endoscopic and radiologic evidence of complete or near complete response. Surveillance flexible sigmoidoscopies were delayed in 63% (n=15/24) of cases. Delays to CT/PET and MRI surveillance were seen in 33% (n=6/18) and 34% (n=11/32) of scans respectively. Conclusions: In this regional setting, enrolments in the W&W approach were appropriate, but delays to surveillance investigations (especially flexible sigmoidoscopy) were common. Specialist colorectal cancer nurses may assist in protocolised surveillance, to overcome both hospital and patient related delays.